1993
DOI: 10.1177/026988119300700403
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine, a better reference drug for panic/agoraphobia. II. Psychomotor and cognitive effects

Abstract: The present reference drugs for the treatment of panic disorder and agoraphobia are imipramine and alprazolam. The latter decreases performance and cognitive functioning. No study of such functions in panic/agoraphobia is available. Fifty four out-patients meeting DSM-III-R criteria for panic disorder with or without agoraphobia (PAG), taking part in a parallel groups controlled trial of imipramine (mean dose ±SEM 114±9 mg), clomipramine (50±4 mg) and propanteline (active placebo) over 8 weeks, were studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…[139] c Ref. [94] analysed by the Blanchards). Intermediate defensive distances can be equated with phobic avoidance.…”
Section: Defensive Distancementioning
confidence: 99%
“…[139] c Ref. [94] analysed by the Blanchards). Intermediate defensive distances can be equated with phobic avoidance.…”
Section: Defensive Distancementioning
confidence: 99%
“…The development of animal models is crucial to investigate the underlying neural mechanisms involved the weight gain produced by antidepressants drugs. Clomipramine was chosen for the present study due to the following reasons: (i) it has high potential to induce weight gain 2) ; (ii) it is a reference drug for treatment of emotional disorders such as obsessive-compulsive disorder and panic disorder 23) and (iii) it has been widely used for treatment of psychiatric disorders as well as in clinical researches in Brazil [24][25][26][27][28] and recent evidence from our research group has indicated that CMI induces weight gain in healthy volunteers (results not published). Long-term treatment with clomipramine (CMI), a tricyclic antidepressant, induces food craving and body weight gain in patients.…”
Section: )mentioning
confidence: 99%
“…No significant drug effects were observed after 8 weeks of treatment with clomipramine (mean dose 50 mg/day), imipramine (mean dose 114 mg/day) and active placebo (Marcourakis et al 1993). In a subsequent study, we evaluated the consequences of chronic use (around 6 years) of therapeutic doses of clomipramine (mean dose 57 mg/day) on remitted out-patients with panic disorder/agoraphobia compared to healthy volunteers matching the patients' characteristics (Carvalho et al 2002).…”
Section: Introductionmentioning
confidence: 97%